Еволюційні тренди в системі інвестиційних і пенсійних фондів в Україні - Коваленко, Юлія Михайлівна; Коваленко, Ірина Ігорівна; Kovalenko, Yuliia Mykhailivna; Kovalenko, Iryna Ihorivna (Економічний вісник, 2020)
У статті досліджено специфічні особливості етапів становлення та розвитку системи інститутів спільного інвестування (далі-ІСІ) та недержавних пенсійних фондів (далі - НПФ) в Україні. Виокремлено такі етапи розвитку ІСІ та НПФ: 1) формування ринкових механізмів торгівлі цінними паперами; 2) формування ринково зорієнтованої взаємодії учасників ринку цінних паперів; 3) формування інноваційно активної взаємодії учасників ринку цінних паперів; 4) забезпечення фінансової безпеки. Виявлено основні системні проблеми у діяльності ІСІ та НПФ. Запропоновано напрями активізації діяльності вітчизняних інвестиційних і пенсійних фондів.

The development of co-investment institutions and non-state pension funds in Ukraine remains not dynamic enough, which is explained by the shortcomings in their legal and informative provision. However, it should be borne in mind that institutional reforms in the field of co-investment are stretched over time and occur in a particular institutional environment, which is often not taken into account. The purpose of the article is to identify the stages of formation and development of investment and pension funds, assessing their specific features, as well as the main problems and areas of activation of the activities of participants in the joint venture industry. The article is based on general scientific methods of cognition, i.e. the analysis and synthesis, functional and system analysis, induction and deduction, historical and logical method, system-structural method, the method of analogy, quantitative and qualitative comparison, graphic, economic and statistical methods of information collection and processing, in particular, sample inquiries, groupings, statistical comparisons of absolute and relative values, the method of logic generalization. The specific features of the stages of formation and development of joint investment institutions and non-state pension funds in Ukraine are investigated in the article. The following stages of development of investment and pension funds are distinguished: 1) formation of market mechanisms of trading in securities; 2) formation of market-oriented interaction of securities market participants; 3) formation of innovatively active interaction of securities market participants; 4) financial security. The main systematic problems in the activity of such funds are revealed. The directions of activation of activity of domestic investment and pension funds are off ered. At the present stage, investment and pension funds are direct competitors of banking institutions in the struggle for financial resources of depositors. The main condition for their further development in Ukraine is full pension reform with the introduction of the second level. Financial policy is devoid of pragmaticity, since it focuses mainly on general wellness measures, which are aimed primarily at improving the legal framework and partly the governance structure. Addressing the issues of further development of joint ventures involves institutionalizing financial processes and increasing institutional confidence in pension and investment funds in general.
Evolutionary trendsin the system of investment and pension funds in Ukraine
Keywords: інститути спільного інвестування; інвестиційні фонди; пенсійні фонди; ринок цінних паперів; цінні папери; фінансові активи; co-investment institutions; investment funds; pension funds; securities market; securities; financial assets